PENGARUH LATIHAN AGILITY TERHADAP GERAKAN SPORT DERAJAT PADA ATLET TARUNG DERAJAT KABUPATEN INDRAMAYU - Alwi, Khamdan; Mubarok, Mochamad Zakky (STKIP Melawi, 2024)
Abstract: This study aims to determine the impact of agility training on sport derajat movements in Tarung Derajat athletes in Indramayu Regency. Using an experimental method, the research involved 16 athletes. The study began with a pretest to measure initial abilities in sport derajat movements, revealing that 12 athletes were rated